Employing Marketing Graduates in MSMEs for Achieving Sustainable Development Goals - Shivany, S.; Jegashini, K.; Dilogini, S. (South Eastern University of Sri Lanka, 2025)
This paper examines the integration of marketing graduates in MSMEs in Sri Lanka, focusing on their contribution to the achievement of SDGs. The study uses a qualitative methodology, collecting data from 30 MSMEs owners and 40 marketing graduates from Northern University. Results show that marketing graduates are increasingly being incorporated into MSMEs, making substantial contributions to specific SDGs. However, limited resources and insufficient skills persist. The study provides insights on how to maximize the performance of marketing graduates and align MSMEs operations with SDGs. Policymakers, academic institutions, and MSMEs managers can better utilize the potential of marketing graduates for sustainable business practices in Sri Lanka. Customized training programs, such as case studies, hands-on seminars, and SDG-related projects, can be developed. Collaboration between universities and MSMEs is also suggested to develop internship programs, research projects, and consulting opportunities that meet both academic learning and real-world business demands.
Keywords: Deployment Practices;Marketing Graduates;Micro, Small, and Medium Enterprises (MSMEs);Sustainable Development Goals (SDGs);Sri Lanka